2020
DOI: 10.1108/ijppm-10-2019-0468
|View full text |Cite
|
Sign up to set email alerts
|

Working capital management, firm performance and nature of business

Abstract: PurposeThis paper aims to investigate the impact of the efficiency of working capital management (WCM) on the performance of a sample of Indian companies and explore how the nature of the firm's business influences the significance and direction of this impact.Design/methodology/approachThe data for this study were collected for the period of 2012–2018 for 414 non-financial firms listed on the Bombay Stock exchange. Fixed-effect regression models were run by taking Tobin's Q and return on equity (ROE) as depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 29 publications
1
42
0
3
Order By: Relevance
“…Taani (2012) found a significant influence of WCM and leverage on the financial performance of Jordanian firms. Similarly, Sawarni et al (2020) investigated Indian nonfinancial firms from 2012 to 2018 and found firms' performance had a considerable effect from WCM efficiency and leverage. Goel and Sharma (2015a) concluded a negative association between leverage and WCM efficiency of manufacturing firms in India for over ten years.…”
Section: Working Capital Management Efficiencymentioning
confidence: 99%
“…Taani (2012) found a significant influence of WCM and leverage on the financial performance of Jordanian firms. Similarly, Sawarni et al (2020) investigated Indian nonfinancial firms from 2012 to 2018 and found firms' performance had a considerable effect from WCM efficiency and leverage. Goel and Sharma (2015a) concluded a negative association between leverage and WCM efficiency of manufacturing firms in India for over ten years.…”
Section: Working Capital Management Efficiencymentioning
confidence: 99%
“…The results revealed an unfavourable association between ROA and the cash conversion cycle. Notably, the difference in Tobin's Q model shows that CCC had no meaningful impact on companies' net worth (Sawarni et al, 2020). Because specific historical studies have observed and show that the management of working capital by the organization (which results in a reduced cash conversion cycle) leads to increased accounting efficiency, this work argues that:…”
Section: Cash Conversion Cycle and Firm Financial Performancementioning
confidence: 93%
“…The longer the CCC, the higher the assets that are in WC. Accordingly, the situation is important to discover a proper plus advance achievement (result) portion which clearly and straightly describes the influence of the companies' WC productivity (Sawarni et al, 2020). Several investigations identified the CCC's influence on the business' financial achievements (Seth et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dari sudut pandang internal perusahaan tentang pengelolaan modal kerja, pada periode setelah terjadi defisit neraca posisi CR menduduki posisi yang lebih baik dibandingkan dengan posisi periode sebelum defisit neraca. H6 : Pengaruh RCP, ICP, PDP, CCC dan CR terhadap kinerja perusahaan sebelum dan setelah defisit neraca perdagangan Penelitian lain yang memperkuat hasil pengujian hipotesis 6 dilakukan oleh Sawarni et al, (2020) dimana variabel independen secara bersama sama memiliki pengaruh signifikan terhadap kinerja perusahaan. Pengelolaan modal kerja tidak dapat dipisahkan dari kelebihan aset lancar.…”
Section: Pembahasan Hipotesisunclassified